2 - Nurturing the Fourth Generation: Defining the Historical Mission for Our Generation: Mshaï S. Mwangola - Mshaï S. Mwangola (Africa Development, 2008)
Reflections on the African academy have identified different generations of African scholars. These interventions have sought to using different criteria, identifying different foci and arguing the importance of each. This paper fur- thers Thandika Mkandawire’s reflection on the first three generations of the post-colonial era (1995) by suggesting a historical mission for the next, the emerging fourth generation.